Analysis of Planning for the First Phase of the Transfer of State Civil Apparatus (ASN) to the National Capital (IKN) of Nusantara at Nusantara Capital Authority - Muhammad Hikmah; Hamka Hamka; Mala Sondang Silitonga (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to determine the implementation of planning for the first stage of moving State Civil Apparatus (ASN) to the National Capital (IKN) of Nusantara and to find out various strategies in overcoming obstacles to planning the transfer of State Civil Apparatus (ASN) to the National Capital (IKN) of Nusantara. This type of research is descriptive qualitative which seeks to explain in as much detail as possible the research objects and problems based on facts in the field. There are three methods for collecting data used in this research, namely: observation, interviews or interviews, and documentation. The results of this research show that in general The overall planning for the transfer of ASN to IKN Nusantara by referring to the ideas of Snell and Morris (2019) has been carried out well, namely; Vision, mission and values, external and internal analysis, formulating and implementing strategies, and evaluation. All of these indicators are parameters for planning the transfer of ASN to IKN Nusantara, which has been implemented well, although improvements are still needed in several aspects. The planning strategy for transferring ASN to IKN Nusantara can then be provided with a persuasive communication model as well as providing various financial stimuli.